Applying a "medical deserts" lens to cancer care services in the North-West region of Romania from 2009 to 2022 - a mixed-methods analysis - Monica Georgiana Brînzac; Marius Ionuț Ungureanu; Cătălin Ovidiu Baba (BMC, 2024)
Abstract Background Medical deserts pose significant challenges to healthcare systems worldwide, leading to unmet healthcare needs and exacerbated health issues, particularly in underserved regions. Methods This study aims to characterise cancer care services in the North-West region of Romania through the lens of medical desertification, employing a mixed-methods approach. Quantitative analysis - descriptive statistics - of secondary data from the Activity of Healthcare Units reports from 2009 to 2022, along with qualitative data - thematic analysis - from interviews with cancer patients and healthcare professionals, were employed to uncover the current state of cancer care in Romania. Results The qualitative analysis highlighted the prevalence of medical deserts in oncology, with inadequate human resources, facility deficiencies, prolonged waiting times, high costs, and socio-cultural barriers hindering access to cancer care. Opportunities for action include revising treatment protocols, enhancing palliative care, implementing prevention strategies, promoting collaboration among healthcare professionals, and digitalising the healthcare system. However, challenges persist, including a shortage of oncology specialists, geographical disparities in cancer prevalence, and limited access to advanced treatment modalities in rural areas. Conclusions Addressing medical deserts in cancer care requires comprehensive approaches, including strategic resource allocation, workforce development, infrastructure investments, access to innovative treatments, and digital health technologies. Collaboration among policymakers, healthcare providers, and communities is crucial to mitigating medical deserts and improving cancer outcomes. Despite limitations, this study provides valuable insights into cancer care services and underscores the need for concerted efforts to overcome medical desertification and ensure equitable access to high-quality cancer care.